Hepatocellular carcinoma progression mediated by hepatitis B virus-encoded circRNA HBV_circ_1 through interaction with CDK1 - Min Zhu; Zi Liang; Jun Pan; Xing Zhang; Renyu Xue; Guangli Cao; Xiaolong Hu; Chengliang Gong (Elsevier, 2021)
Hepatitis B virus (HBV) produces circular RNA (circRNA), whose functions have not yet been clearly elucidated. In this study, a novel circRNA HBV_circ_1 produced by HBV was identified in HBV-positive HepG2.2.15 cells and HBV-related hepatocellular carcinoma (HCC) tissue (HCCT). Microarray analysis of 68 HCCT samples showed that HBV_circ_1 abundance was significantly higher than that in paracancerous tissues. In addition, survival rate of HBV_circ_1-positive patients was significantly lower compared with HBV_circ_1-negative patients. Transient expression indicated that HBV_circ_1 enhanced cell proliferation, migration, and invasion and inhibited apoptosis in vitro. Furthermore, ectopical HBV_circ_1 expression increased tumor size in vivo. HBV_circ_1 was confirmed to interact with cyclin-dependent kinase 1 (CDK1) to regulate cell proliferation. These results suggest that HCC progression may be promoted by interaction of HBV_circ_1 with CDK1. Our data not only showed a novel clue to understand carcinogenesis and progress of HBV-related HCC but also provided a new target for the development of therapeutic drugs.